2013
DOI: 10.5194/gi-2-55-2013
|View full text |Cite
|
Sign up to set email alerts
|

Towards a muon radiography of the Puy de Dôme

Abstract: Abstract. High-energy (above a few hundred GeV) atmospheric muons are a natural probe for geophysical studies. They can travel through kilometres of rock allowing for a radiography of the density distribution within large structures, like mountains or volcanoes. A collaboration between volcanologists, astroparticle and particle physicists, TOMUVOL was formed in 2009 to study tomographic muon imaging of volcanoes with high-resolution, large-scale tracking detectors. We report on two campaigns of measurements at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Since the pioneering works by Nagamine (1995Nagamine ( , 2003, Nagamine et al (1995) and Tanaka et al (2001), recent studies have illustrated the interest of the method in imaging spatial and temporal variations of the density inside mountains and volcanoes (Tanaka et al 2005(Tanaka et al , 2007a(Tanaka et al , b, 2008(Tanaka et al , 2009a(Tanaka et al , b, 2013Gibert et al, 2010;Cârloganu et al, 2013;Lesparre et al, 2010Lesparre et al, , 2012cShinohara and Tanaka, 2012;Eppelbaum and Khesin, 2012;Carbone et al, 2014). Muon radiography is a straight-ray transmission method involving a Radon transform that markedly differs from the 3-D integrative gravity method.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering works by Nagamine (1995Nagamine ( , 2003, Nagamine et al (1995) and Tanaka et al (2001), recent studies have illustrated the interest of the method in imaging spatial and temporal variations of the density inside mountains and volcanoes (Tanaka et al 2005(Tanaka et al , 2007a(Tanaka et al , b, 2008(Tanaka et al , 2009a(Tanaka et al , b, 2013Gibert et al, 2010;Cârloganu et al, 2013;Lesparre et al, 2010Lesparre et al, , 2012cShinohara and Tanaka, 2012;Eppelbaum and Khesin, 2012;Carbone et al, 2014). Muon radiography is a straight-ray transmission method involving a Radon transform that markedly differs from the 3-D integrative gravity method.…”
Section: Introductionmentioning
confidence: 99%
“…For the application of muography, several types of detector have been used, such as a scintillation type (e.g., Tanaka et al, 2011a;Lesparre et al, 2012;Anastasio et al, 2013), a gas chamber type (e.g., Barnaföldi et al 2012;Cârloganu et al, 2013), and an emulsion type (Tanaka et al, 2007). The greatest advantage of the emulsion detectors is that they are portable and do not require electricity to operate.…”
Section: Nuclear Emulsion Detectormentioning
confidence: 99%
“…3, the differential flux is plotted within an energy range between 10 MeV and 1 TeV. Electrons with energies above 10 MeV can penetrate a 5 cm thick plastic scintillator; thus, these components could be background sources when thin plastic scintillators (e.g., Lesparre et al, 2012) or gaseous detectors (e.g., Cârloganu et al, 2013;Oláh et al, 2012) are used for muography observations. If the angular resolution of a muography telescope is not enough to distinguish these components from muons, these electrons and positrons scatter in the air, change direction, and become a possible source of background events.…”
Section: Scattering Of Decay Electrons In the Atmospherementioning
confidence: 99%
“…1). Although Cârloganu et al (2013) located their telescope at a distance of 2 km from the peak of the Puy de Dôme volcano, they reported that the background noise dominated the muon flux when the rock thickness exceeded 1 km. Such short-range muography is practical when the target volcanoes are dormant or less active.…”
Section: Introductionmentioning
confidence: 99%